EVALUATION OF ALLELOPATHIC POTENTIAL OF LEAF EXTRACT OF KIELMEYERA CORIACEA ON LACTUCA SATIVA L - Marinho dos Santos, Valter Henrique [UNESP]; Daneluzzi, Gabriel Silva; Silva, Luciana Pereira; Goncalves da Silva, Regildo Marcio [UNESP] (Univ Federal Uberlandia, 2015)
Kielmeyera coriacea Mart. (Clusiaceae), popularly known as pau-santo, is a typical Brazilian cerrado tree known due to its varied secondary metabolites. This study aimed to determine the allelopathic potential of the hydroalcoholic extract of leaves of K. coriacea through bioassays of seed germination, seedling growth and mitotic index of Lactuca sativa L. (lettuce). In addition it was done the tetrazolium assay and a phytochemical screening. The extract concentrations caused alterations in germination parameters, in root growth and in the mitotic index. The phytochemical screening showed the presence of triterpenes, coumarins, steroids, flavonoids and condensed tannins, compounds known to confer allelopathic characteristics upon other species. These data indicate that K. coriacea presents an allelopathic potential because its leaf extracts interfere with germination and growth without any interference of pH and osmotic potential in the results.
Keywords: Kielmeyera coriacea; Germination Parameters; Mitotic Index; Phytochemical Screening; Seedling Growth